ABU TUMIN: BIOGRAFI ULAMA DAYAH ACEH (1932-2017) - Muammar .; Mawardi .; Husaini . (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2018)
ABTRASCTThe research entitled "Abu Tumin: Biography Of Dayah Scholars In Aceh, 1932-2017" raises the question of how Abu Tumin's life journey became a scholar of great influence in Aceh. This study aims to find out the life of Abu Tumin which includes, family background, education of Abu Tumin, Abu Tumin leads Dayah Madinatuddiniyah Babussalam Blang-Bladeh and also includes factors supporting Abu Tumin becoming a scholar viewed from family factors, cultural factors as well as social and environmental social factors. The method used is historical method with qualitative approach, while the data collection using the technique of ratearch library (literature study) and filed risearch that includes observation, documentation and interview. Based on the research that has been done, the results obtained as follows: Abu Tumin is an Acehnese ulama who has a lineage of religious experts. From a small Abu Tumin has been introduced to the science of religion by his father, Teungku Young Leube. For now Abu Tumin is seen as one of the oldest clerics in Aceh and one of Abuya Muda's surviving Waly Al-Khalidy students. Abu Tumin is a cleric who has considerable influence and followers in Aceh. His opinion regarding polemic settlement in society is still highly prioritized, especially concerning religious issues, so he is known as one of Aceh's charismatic clerics. Keywords: Abu Tumin, Biography, Scholars, Dayah.